Preservation versus non-preservation of left colic artery in colorectal cancer surgery: An updated systematic review and meta-analysis - Yang, Xuyang (Medicine (Baltimore), 2019)
BACKGROUND: It remains unclear whether or not preservation of the left colic artery (LCA) for colorectal cancer surgery. The objective of this updated systematic review and meta-analysis is to evaluate the current scientific evidence of LCA non-preservation versus LCA preservation in colorectal cancer surgery. METHODS: A systematic search was conducted in the Medline, Embase, PubMed, Cochrane Library, ClinicalTrials, Web of Science, China National Knowledge Infrastructure and Chinese BioMedical Literature Database, and reference without limits. Quality of studies was evaluated by using the Newcastle–Ottawa scale and the Cochrane Collaboration's tool for assessing the risk of bias. Effective sizes were pooled under a random- or fixed-effects model. The funnel plot was used to assess the publication bias. The outcomes of interest were oncologic consideration including the number of apical lymph nodes, overall recurrence, 5-years overall survival, and 5-years disease-free survival (DFS); safety consideration including overall 30-day postoperative morbidity and overall 30-day postoperative mortality; anatomic consideration including anastomotic circulation, anastomotic leakage, urogenital, and defaecatory dysfunction. RESULTS: Twenty-four studies including 4 randomized controlled trials (RCTs) and 20 cohort studies with a total of 8456 patients (4058 patients underwent LCA non-preservation surgery vs 4398 patients underwent LCA preservation surgery) were enrolled in this meta-analysis. The preservation of LCA was associated with significantly less anastomotic leakage (odds ratio 1.23, 95% confidence interval 1.02–1.48, P = .03). In term of sexual dysfunction, urinary retention, the number of apical lymph nodes, and long-term oncologic outcomes, there were no significant differences between the LCA non-preservation and LCA preservation group. It was hard to draw definitive conclusions on other outcomes including operation time, blood loss, the first postoperative exhaust time, and perioperative morbidity and mortality for insufficient data and highly significant heterogeneity among studies. CONCLUSIONS: The pooled data provided evidence to support the LCA preservation preferred over LCA non-preservation in anastomotic leakage. Future more large-volume, well-designed RCTs with extensive follow-up are needed to draw a definitive conclusion on this dilemma.